The Design of Electronic Filter Training for Accountant and Lawyer Staffs From E-Procurement Finance Crime - Pamuji, Wirawan; Anton Hutomo Sugiarto; Putri Ridhotul Uliyah (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
The Tender Demand with Electronic site is Important for Regional Government and its official as therefore could sustain advance stabilization within the region but very difficult to operate without media to sustain It.  The Beneficences about the application of the Electronic Order, beside can minimize the time, it also can also a vested interest for supplier participates towards Public need as observed by R and D Method. But in that way there is a fraud as a way of doing against law, the crimes is an indication against Nation Will to create stability the situation. The State Institution observes line of Good Purchase ordered by E- fraud